Software Defined Internet of Everything - Aujla, Gagangeet Singh; Garg, Sahil; Kaur, Kuljeet; Sikdar, Biplab (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides comprehensive discussion on key topics related to the usage and deployment of software defined networks (SDN) in Internet of Everything applications like, healthcare systems, data centers, edge/fog computing, vehicular networks, intelligent transportation systems, smart grids, smart cities and more. The authors provide diverse solutions to overcome challenges of conventional network binding in various Internet of Everything applications where there is need of an adaptive, agile, and flexible network backbone. The book showcases different deployment models, algorithms and implementations related to the usage of SDN in Internet of Everything applications along with the pros and cons of the same. Even more, this book provides deep insights into the architecture of software defined networking specifically about the layered architecture and different network planes, logical interfaces, and programmable operations. The need of network virtualization and the deployment models for network function virtualization is also included with an aim towards the design of interoperable network architectures by researchers in future. Uniquely, the authors find hands on practical implementation, deployment scenarios and use cases for various software defined networking architectures in Internet of Everything applications like healthcare networks, Internet of Things, intelligent transportation systems, smart grid, underwater acoustic networks and many more. In the end, design and research challenges, open issues, and future research directions are provided in this book for a wide range of readers. Presents a variety of applications of software defined networks (SDN) in smart communities with different viewpoints; Includes practical models, algorithms and implementations of SDN and IoT; Features detailed implementation of adaptive SDN algorithms along with evaluation results.
Part I Internet of Everything and Smart City -- Internet of Everything: Background and Challenges -- Smart Cities, ConnectedWorld and Internet of Things -- Part II Software-defined Networking -- "Challenges of Traditional Networks and Development of Programmable Networks" -- Architecture and Deployment Models-SDN protocols, APIs, and Layers, Applications and Implementations -- Network Policies in Software Defined Internet of Everything -- Analysis of Load Balancing Techniques in Software-defined Networking -- Analysis of Energy Optimization Approaches in Internet of Everything: An SDN Prospective -- Network Function Virtualization -- Part III Application of Software-defined Networking in Cloud Computing -- "Prospective on Technical Considerations for Edge-Cloud Cooperation using Software Defined Networking" -- Software-Defined Networking in Data Centers -- QoS-Aware Dynamic Flow Management in Software-Defined Data Center Networks -- Part IV Security and Trust Applications for Software-defined Networking -- Trusted Mechanism using Artificial Neural Networks in Healthcare Software-Defined Networks -- Stealthy Verification Mechanism to Defend SDN Against Topology Poisoning -- Implementation of Protection Protocols for Security Threats in SDN -- Part V Application Use Cases of Software-defined Networking -- SDVN Based Smart Data Dissemination Model for High Speed Road Networks -- Advanced Deep Learning for Image Processing in Industrial Internet of Things under Software Defined Network.
Keywords: Cooperating objects (Computer systems).; Telecommunication; Application software; Cyber-Physical Systems; Communications Engineering, Networks; Computer and Information Systems Applications